Impact of Entrepreneurship Training on Entrepreneurial Efficacy and Alertness among Adolescent Youth - Ho, Moon-Ho Ringo; Uy, Marilyn A.; Kang, Bianca N. Y.; Chan, Kim-Yin (Frontiers in Education, 2018)
Our study focuses on the impact of systematic entrepreneurship training comprising both active and passive learning activities on entrepreneurial alertness and efficacy among adolescent youth. Reports from a two-wave online survey among 328 students from five secondary schools (aged 13-16 years; 34.8% male and 65.2% female) reveal that those who went through entrepreneurship training (treatment group, N=142) had significantly higher entrepreneurial alertness and efficacy levels compared to those who did not go through training (control group, N=186). We also find that even with gender effects accounted for, the higher entrepreneurial alertness and efficacy levels in the treatment group are due in part to both passive and active/hands-on elements of the program. Our study offers direct evidence that conducting entrepreneurship training programs among secondary school students could be an effective means to enhance entrepreneurial competencies among the youth. Specifically, our findings highlight the value of entrepreneurial training in improving age-appropriate competencies of entrepreneurial alertness and efficacy.